دراسة ميدانية على شركة الخطوط الجوية الجزائرية :covid-: Factorial structure of the leadership practices during the crisis of Covid-19 pandemic Case study Air Algerie company - تباني رزيقة (Journal of North African Economies, 2025)
This study aimed to explore the factorial structure of Leadership practices during COVID-19 pandemic scale at the Air Algerie Company, on a sample of 150 individuals who responded to the study’s objectives, working in four regional agencies affiliated to the company. The validity and reliability of the scale were confirmed on a sample of 50 individuals, while the answers of the remaining sample (100 individuals) were subjected to exploratory factor analysis using the principal components method (PCA) and orthogonal rotation by varimax, resulted in extracting 3 factors, explained a percentage of 74.13% of the total variance, and were named as follows: The first factor “Organizational flexibility and demonstrating empathy with the human tragedy”, the second factor “Maintain transparency collaborate and Communicating effectively with stakeholder” , the third factor is “Empowerment, calmness, bounded optimism and ability to making decisions amid uncertainty” .